Lobular breast cancer in men: case report and review of the literature. - Mariolis-Sapsakos, Theodoros; Theodoropoulos, George; Flessas, Ioannis I; Orfanos, Filotheos; Orfanos, Nikolaos; Konstantinou, Evangelos A; Konstadinou, Evangelos; Zagouri, Flora; Vlachodimitropoulos, Dimitris; Zografos, George C (Onkologie, 2010)
BACKGROUND: Lobular breast cancer in men is an extremely infrequent occurrence due to the lack of lobules and acini in the male breast. Such a rare case is described here. CASE REPORT: A 74-year-old patient presented with a sizeable lesion in the right breast, which proved to be a lobular carcinoma. Genetic studies excluded Klinefelter's syndrome, though revealing an interesting genetic multiformity feature. This case represented a lobular carcinoma in a genotypically male patient under no exogenous or endogenous estrogenic influence. CONCLUSIONS: The increasing number of male lobular breast cancer cases should be explored more extensively with particular emphasis placed on causally related genetic and hormonal factors.
Keywords: Aged; Biopsy, Fine-Needle; Breast; Breast Neoplasms, Male; Carcinoma, Lobular; Chemotherapy, adjuvant; Combined Modality Therapy; Humans; Karyotyping; Male; Mastectomy, Modified Radical; Neoplasm Invasiveness; Neoplasm Staging